Synergistic Effects of Doxorubicin and Cardenolid Glycosides of Calotropis Gigantea Root on Cervical Cancer Hela Cell Line - Roihatul Mutiah; Risma Aprinda Kristanti; Siti Maimunah (Faculty of Pharmacy, Universitas Gadjah Mada, 2017)
Cardenolid glycosides (CGs) has been known has high anticancer activity against several types of cancers, for example, breast cancer, lung cancer, prostate cancer, melanoma, neuroblastoma, myeloma and leukemia in the in vitro and in vivo research. The aim of our study was to know the synergistic potency of CGs improving the efficacy of doxorubicin in cervical cancer. Activities from combination of doxorubicin and CGs was measured by MTT colorimetric methode. Combination Index was used as combination efficacy parameter. The results showed that the IC50 of CGs was 1,023 μg/mL. CGs demonstrated selective activity in inhibiting the growth of HeLa cells by selectivity index > 3 (241.9). Combination test for CGs and Doxorubicin showed strong synergistic effect in doses 200 ug/mL Doxorubicin and 1.79 ug/mL CGs. The synergistic effect has been shown by 10 combination doses for the doses below the IC50. CGs increases the efficacy of Doxorubicin for the doses below the IC50, thus CGs can be recommended as co chemotherapy in cervical cancer treatment.